An evaluation on attitudes of students, receiving English preparatory education, towards English course - Temur, Mehmet; Tuncer, Murat (My University, 2018)
The main aim of this research is to evaluate the attitudes of students, receiving English Preparatory Education (EPE), towards English courses. This work was carried out based on survey research model. According to the findings gained by means of discriminant analysis, we can make a collocation among learners’ attitudes depending on their income levels that were displayed in portional of horizontal average as low, middle and high. In particular, it was reached with figure %52,3 among the learners whose income level was illustrated as middle. Finally, when the attitudinal descriptive measure instrument was put into consideration during the educational- teaching proccesses, we can suggest an other more functional measuremental instrument that can be used instead of attitunal, or that’s to say, it can be concluded that there is an other variance which can better percieve income measurement to collocate the findings in more correct figures %52,3 of research.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: English course; Attitude; Preparatory education; English education